Society and change - Krishnaswamy, K .S. (ed.); Mitra, Ashok; Patel, I.G.; Raj, K.N.; Srinivas, M.N. (Bombay, Oxford University Press, 1977)
This volume contains the essays that were, sooner or later, received, Bearing in mind that Sachin's circle of friends included economists, scientists, politicians, poets, artists and philosophers, we suggested to the contributors that they may explore aspects of social development which in their view Sachin's life had illuminated and enlarged. We have not tried to fit the different pieces into any single thesis; this, in our view, would have run counter to the spirit of Sachin's eclectic approach. For Sachin, development was essentially an acceleration of the process of social regeneration. While the stimulus for such regeneration could come from a variety of sources, both historical and current, its fulfilment was to be found in the manifestation not just of material growth but of cultural progress and aesthetic achievement as well. In the final analysis, development had to do with the clarification and achievement of social values which F10 enhanced the dignity of the individual while ensuring social justice and integrity.
Essays in Honour of Sachin Chaudhuri
Keywords: Social change